RANCANG BANGUN HEALTH MONITORING SYSTEM BERBASIS INTERNET OF THINGS (IoT): ESP8266 DAN BLYNK - Juju Juhaeriyah; Edo Agung N; Rindi Wulandari (Komunitas Dosen Indonesia, 2023)
Health monitoring is important for living creatures. There are many things that are important factors in the health of living creatures, especially humans, including heart rate, body temperature and oxygen saturation. IoT technology is very helpful in the development of health technology so that it becomes possible to monitor patient health in real time and patient emergency information can be accessed easily. This research also aims to design an Android-based heart rate monitoring system using ESP8266 as a microcontroller. The sensor used is Max30102. The research method used is applied research, with experimental research methods. The research stages carried out were literature study, software design, hardware design, system testing, and analysis. The results of the research are the design of a patient health monitoring tool with three measured indicators, namely the patient's heart rate, body temperature and oxygen levels. The system can monitor in real time based on Internet of Things and can be accessed by Android and iOS. From the study results, it was found that the Android-based health monitoring system has an accuracy rate of 97.63% and it can be said that the system can be used for patient measurements. With details, 96.71% is the accuracy level for measuring heart rate, 96.45% accuracy level for measuring oxygen levels in the patient's body, and 99.75% accuracy level for measuring patient temperature.